Exploration of the Implementation of the Movement Method in Memorizing Hadith in Children: A Case Study at Tadika Al Fikh Orchard Pendamar Indah - Hasibuan, Juli Khairani; Mavianti, Mavianti (PT ARRUS Intelektual Indonesia, 2024)
Every issue that people face in their lives can be resolved by using Hadis as a guide to life. It contains ideas that people must constantly comprehend in order to use them in their daily lives. Researchers employ a sort of study known as classroom action research, or simply classroom action research. This study took a qualitative, descriptive approach to its methodology. The teacher assigns this task during the learning process, and the student completes it. The goal of classroom action research (PTK) is to address real-world issues that arise in the classroom and boost teachers' actual professional development activities. Following the observation and interview phases and the application of the Movement method, 99% of students were able to comprehend the hadith, with the remaining 1% finding it easy to apply but forgetting it later and needing to repeat it frequently to improve their memorization. It is possible to draw the conclusion that the Movement method can have greater effect than the previous approach based on the findings of the research and the outcomes of the procedure that the researchers used. increased capacity for memorizing in Tadika Al Fikh Orchard Pendamar Indah, Klang, Selangor, Malaysia's hadith classes. This, along with the interview's findings, demonstrates how well the pupils comprehend the implementation of the Movement method in memorizing hadis.